PENGGUNAAN MODEL PEMBELAJARAN AKTIF TIPE QUIZ TEAM DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK SMA NEGERI 13 MAKASSAR - Nurlina Nurlina (Jurnal Education, 2025)
One of the efforts to improve students' mathematics learning outcomes is by using the Quiz Team type active learning model. This study aims to determine and describe the effectiveness of mathematics learning through the use of the Quiz Team type learning model on the mathematics learning outcomes of students at SMA Negeri 13 Makassar. This type of research uses Classroom Action Research (CAR). Sampling was carried out by Simple Random Sampling. The research instruments used consisted of student activity observation sheets and learning outcome tests. Based on the results of the study, it was found that the Use of the Quiz Team Type Active Learning Model was effective in improving the mathematics learning outcomes of students at SMA Negeri 13 Makassar. This can be seen from the significant increase in students' mathematics learning outcomes by implementing the Quiz Team Type Active Learning Model. This can be seen from the high increase in the average value of students' mathematics learning outcomes before and after treatment. In the pre-test, the completion rate was only 35%, while the completion rate in cycle I was 61% and in cycle II increased to 91%, this shows a significant increase in learning outcomes.